Soil Monitoring Equipment and Automatic Springers Using Soil Moisture Sensor on Okra Plant at Ikahi Raya Plantation - Desy Rahmadani Purba; Melly Nazwa Juwita (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
In this modern era, automatic plant sprinklers are important for important plants, coupled with the busyness of plant owners in caring for plants, watering plants manually is not practical, because homeowners have to come to the garden and water the plants directly using energy. The owner also cannot leave the plant for a long period of time, because the plant can lack water and cause the plant to wither or even die. Currently, the ease and efficiency of time and energy are the main considerations for humans in carrying out activities. From time to time we are faced with rapid technological developments, making human work easier. Therefore, this tool is designed to use a soil moisture sensor (soil moisture sensor) as a detector of soil conditions on plants by means of sensors detecting wet or dry soil and when the soil is wet the pump is ON to automatically water the plants. Plant owners can also monitor plants with LCD (Liquid Crystal Display) and blynk to know soil moisture conditions and their status through plants. This of course can make plant owners more effective in saving energy and time in caring for plants.